Performance and Potential of Central Government Revenue: A Panel Data Analysis for Oil Exporting and Importing Countries - Waheed, Abdul; Saqib, Najia (International Journal of Energy Economics and Policy, 2019)
The main goal of every government in the country is to promote economic and social development. The fulfillment of this goal depends on the availability of sufficient amount of central government revenue. Unfortunately, in developing countries, the collection of revenue is far below than expectations. This study initiated with twin objectives. First, to identify the macroeconomic variables that affects central government revenue and examines their importance. Second, to access the performance and potential of revenue collection by the central government of oil- exporting and importing countries. The panel data estimation results of a sample of 22 oil-exporting countries for the period 2004-2017, identified several important macroeconomic variables that significantly affect central government revenue. It is also concluded that some countries are very poor in revenue generation compare to what we expect based on macroeconomic performance of some indicators. It is also observed that some oil-exporting and importing countries could not maintain their revenue generation performance and are facing serious problem to finance their expenditures. Keywords: Central Government Revenue, Economic Development, Panel Data, Oil Exporting and Importing Countries, Revenue Performance of Government JEL Classifications: H20, F63, C23, O57, H11 DOI: https://doi.org/10.32479/ijeep.8819